KEY INTERACTIONS FOR CLATHRIN COAT STABILITY - Böcking, Till (2014)
Clathrin-coated vesicles are major carriers of vesicular traffic in eukaryotic cells. This endocytic pathway relies on cycles of clathrin coat assembly and Hsc70-mediated disassembly. Here we identify histidine residues as major determinants of lattice assembly and stability. They are located at the invariant interface between the proximal and distal segments of clathrin heavy chains, in triskelions centered on two adjacent vertices of the coated-vesicle lattice. Mutation of these histidine to glutamine alters the pH dependence of coat stability. We then describe single-particle fluorescence imaging experiments in which we follow the effect of these histidine mutations on susceptibility to Hsc70-dependent uncoating. Coats destabilized by these mutations require fewer Hsc70 molecules to initiate disassembly as predicted by a model in which Hsc70 traps conformational distortions during the auxilin- and Hsc70:ATP-mediated uncoating reaction.